Occurrence and role of lung megakaryocytes in infection and inflammation - Gelon, Lucie; Fromont, Léa; Lefrançais, Emma (Frontiers in Immunology, 2022)
Megakaryocytes (MKs) are large cells giving rise to platelets. It is well established that in adults, MKs develop from hematopoietic stem cells and resides in the bone marrow. Megakaryocytes are also rare but normal constituents of the venous blood returning to the lungs and megakaryocytes are found in the lung vasculature (MKcirc) suggesting that these cells are migrants from the bone marrow and get trapped in lung capillaries were the final steps of platelet production can occur. An unprecedented increase in the number of lung and circulating megakaryocytes was described in Covid-19 patients suggesting that lung thrombopoiesis may be increased during lung infection and/or thromboinflammation. In addition to the population of platelet-producing intravascular megakaryocytes in the lung, a population of resident lung megakaryocytes (MKL) has been identified and present a specific immune signature compared to their bone marrow counterparts. Recent single cell analysis and intravital imaging have helped us gain a better understanding of these populations in mouse and human. This review aims at summarizing the recent data on increased occurrence of lung MKs and discusses their origin, specificities and potential role in homeostasis, inflammatory and infectious lung diseases. Here we address remaining questions, controversies and methodologic challenges for further studies of both MKcirc and MKL.